PORTRAYING TEACHER-STUDENT'S INTERACTION IN EFL CLASSES : A Case Study in 7TH and 8th EFL - CLT based classroom - Setiawati, Liani (2013)
The objective of EFL classes adopting Communicative language teaching (CLT) approach is to be fluent and communicative competent in genuine communication (Hatch1978; Nunan, 1987). In this context, EFL teachers play a pivotal role to foster a learning environment which helps engage students in meaningful verbal teacher-students interactions. To facilitate such meaningful interactions, EFL teachers serve as a source of L2 input to the students (Krashen,1981,1985), encourage students to produce target-like output (Swain, 1995) and provide feedbacks and interactional adjustments (Long, 1996) for students as part of the verbal interactions. This study therefore attempts to portray the nature of teacher-student interaction and reveals the factors inhibiting teachers to interact with students. 15 classroom observations were conducted in four months, which involved two EFL teachers, together with their 7th and 8th students. Significant and related data were gained from 6 classroom investigations through classroom audio and video-taping, oral report, questionnaire, interview and field-note. The observations in this study found that EFL teachers performed differently in this context, though the finding confirmed both participants were technically capable of employing various interactional adjustments and providing due feedbacks in teacher-students interactions. Through the questionnaire and interview, it was revealed that such performance variances was related to their belief and perception (Johnson,1999). Apart from personal belief and perception, their performance in engaging meaningful teacher-student interaction was also influenced by their communicative competence which is commonly further broken down in individual competence of linguistic, sociolinguistic, discourse and strategic (Canale& Swain, 1980). The follow up analysis with the participants agreed that teachers' belief and limited communicative competence were likely the causes inhibiting their performance. Communication breakdown and students' confusion were commonly found in both classes. To rectify this situation, it helps if EFL teachers can align their belief with the basic CLT principles, and develop their communicative competence further. Keywords: communicative competence, communicative language teaching, interactional adjustments, communicative interaction